Surface treatments for boriding of Ti6Al4V alloy in view of applications as a biomaterial. (October 2018) - Peretti, V.; Ferraris, S.; Gautier, G.; Hellmich, C.; Lahayne, O.; Stella, B.; Yamaguchi, S.; Spriano, S.
Abstract: Even if Ti6Al4V has great biocompatibility, it cannot be used for several components of joint implants because of low wear and fretting resistance. This research is focused on improving the bio-tribological characteristics of Ti6Al4V alloy through a surface boriding process. The borided coating was characterized by microstructural and chemical analyses, hardness and adhesion tests. Adsorption of albumin was verified by surface zeta potential vs pH for characterizing interaction with physiological natural lubricants. A heat treatment at temperature near or above the beta transus allows to obtain a performant coating (thickness, hardness, adhesion) even if a change in microstructure of the substrate occurs. Highlights: Changes in microstructure of Titanium alloy substrate due to a surface ceramic conversion treatment. Scratch test to evaluate borided coating adhesion on Titanium alloy substrate. Zeta potential analyses carried out on treated Titanium alloy samples before and after soaking in protein solution.